2015
DOI: 10.1038/bmt.2015.165
|View full text |Cite
|
Sign up to set email alerts
|

Patient age, remission status and HCT-CI in a combined score are prognostic for patients with AML undergoing allogeneic hematopoietic cell transplantation in CR1 and CR2

Abstract: For AML, older age, advanced disease and increased hematopoietic cell transplant comorbidity index (HCT-CI) are associated with worse prognosis following allogeneic hematopoietic cell transplantation (HCT). This single-center retrospective study investigated the influence of pre-transplant characteristics on outcomes of 387 patients undergoing allogeneic HCT for AML in CR1 and CR2. The multivariable analysis model for overall survival (OS) included age (hazard ratio (HR) = 2.24 for ages 31-64 years and HR = 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…As shown in other studies, the HCT-CI had a limited capacity to predict disease relapse in our population. (15, 19)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in other studies, the HCT-CI had a limited capacity to predict disease relapse in our population. (15, 19)…”
Section: Discussionmentioning
confidence: 99%
“…The Hematopoietic Cell Transplantation Comorbidity Index (HCT-CI), initially proposed by Sorror and colleagues,(10) has become a widely validated tool to predict outcomes in many transplant settings. This includes children(11) and adults undergoing allo-HCT for various diseases,(1215) as well as in patients receiving different conditioning regimens. (16, 17) This model was initially developed to predict non-relapse mortality (NRM), although it has also been proven useful to stratify patients for the risk of other outcomes including OS,(12) and GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…Several risk scoring systems are available that use patient-specific and diseasespecific factors to make the choice of intensive or alternative treatment. 74,132,133,210 The relevance of systems 193,194 originally designed to forecast NRM after allogeneic HCT is under investigation. 211 Treatment alternatives for unfit patients are limited to best supportive care, low-intensity treatment, or clinical trials with investigational drugs.…”
Section: -209mentioning
confidence: 99%
“…192 Recent reports suggest that a combination of the HCT-CI and the EBMT score may provide improved prediction of NRM and OS. 193,194 New modalities. Partial or complete T-cell depletion and posttransplant cyclophosphamide may reduce the risks of acute and chronic graft-versus-host disease (GVHD).…”
Section: Org Frommentioning
confidence: 99%
“…13 At our center, we recently demonstrated that the HCT-CI, when combined with age and remission status, can stratify AML patients undergoing allogeneic HCT into prognostic risk groups. 14 Although the prognostic value of the HCT-CI score for allogeneic HCT in AML in particular has been demonstrated in some studies, 8,15 the score was not developed as a disease-specific scoring system. The possibility remains that certain comorbidities may exert a different influence on outcomes depending on the indication for which allogeneic HCT is performed.…”
Section: Introductionmentioning
confidence: 99%